Transmission Grid Security A PSA Approach - Haarla, Liisa; Koskinen, Mikko; Hirvonen, Ritva; Labeau, Pierre-Etienne.; SpringerLink (Online service) (London : Springer London, 2011)
In response to the growing importance of power system security and reliability, Transmission Grid Security proposes a systematic and probabilistic approach for transmission grid security analysis. The analysis presented uses probabilistic safety assessment (PSA) and takes into account the power system dynamics after severe faults. In the method shown in this book the power system states (stable, not stable, system breakdown, etc.) are connected with the substation reliability model. In this way it is possible to: estimate the system-wide consequences of grid faults; identify a chain of events that might lead to blackout; and rank the importance of different substation components at the system level. Transmission Grid Security also presents the main features and basic mathematics of PSA. It provides the reader with up-to-date knowledge of the regulatory issues affecting the security of transmission grids in Europe. Transmission Grid Security gives a practical method for the security analysis of transmission grids, making it a valuable text for engineers and system operators, as well as postgraduate students. It includes basic information and detailed modules for creating a reliability model that takes into account all the basic operations and components needed after grid faults.
1. Introduction -- 2. Grid Security $1 (BProblem Statement -- 3. Basic Concepts of Transmission Grid Planning -- 4. Basic Concepts of Reliability Theory -- 5. Grid Faults and Component Failures -- 6. Substation PSA Model -- 7. Dynamic Consequence Analysis -- 8. System level Results -- 9. Perspectives for Future Power System -- 10. Conclusions.s
Keywords: Engineering; System safety; Production of electric energy or power; Engineering; Power Electronics, Electrical Machines and Networks; Quality Control, Reliability, Safety and Risk